Plurilinguismo e traduzione. Tre esempi per una definizione dei confini - BIAGI, DARIA (2014)
The question of multilingualism as a process of textual interplay, rather than a mix of different languages, emerges with unmistakable clarity in the act of translation. Tackling the issue of setting its boundaries, this paper first examines the theoretical and critical definitions of the multilingual literary text in the last decades, and then turns to the analysis of three case studies from the work of the German translator Moshe Kahn, namely Malerba's Il pataffio, Camilleri's Il re di Girgenti and D'Arrigo's Horcynus Orca. The variety of strategies he adopted in translating these three novels shows how the understanding of multilingual writing shifts over time, being closely related to narrative subjects and literary projects.